Back surface reflector optimization for thin single crystalline silicon solar cells - Kopach, V.R.; Kirichenko, M.V.; Shramko, S.V.; Zaitsev, R.V.; Tymchuk, I.T.; Antonova, V.A.; Listratenko, A.M. (Functional Materials, 2007)
It has been shown that for single crystalline silicon solar cells (Si-SC) with 180-200 μm thick base crystals, the optimum back surface reflector (BSR) is TiO₂/Al with 0.18 μm thick oxide layer. At such BSR, the reflection coefficient for photoelectric active sunlight reaching the back surface of Si-SC at 0.88-1.11 μm wavelengths attains 81 to 92 % against of 71 to 87 % at direct Al contact with back surface of silicon base crystal.